Studying the effect of common intestinal parasites on the digestive system of children (Eurasian Journal of Research, Development and Innovation, 2024)
The results of the current study, according to scientific research, showed that approximately 20% of children are infected with intestinal parasites, and that the age group (4-5) years has the highest infection rate.